Proposals for an epistemology of heritage - Feliu Franch, Joan (2018)
The article in twelve principles, proposals to reflect on the reasons that lead people to defend, protect and preserve the heritage. From a philosophical positioning the text addresses the issue of conservation of cultural heritage.